(untitled) (Global Journal of Human-Social Science, 2012)
Zulfiqar Ali Bhutto was the first elected prime minister of Pakistan His initial strategy of accommodation and power sharing with the regionalists in Balochistan had a positive impact on the national politics The regionalists started to distance themselves from secessionist tendencies However the policy of pacification was short-lived The central government instead of addressing political conflicts with consensus resorted to undemocratic means The process of democratization in Balochistan was disrupted and the provincial government was dissolved The autonomists were sidelined and were dubbed as anti-state elements The extremists within the autonomists fold were infuriated and started the armed insurgency The central government launched an army operation to cope with insurgents Bhutto s regime marked a tendency towards executive despotism Despite provincial government s alleged defiance of federal authority the central government could have treated them with patience and tolerance visualizing the sensitivity of the Balochistan crisis